2DEG enhancement via epilayer stress engineering in AlN/GaN/AlN heterostructure - Patwal, Shashank (Nanyang Technological University, 2021)
Over the last couple of decades, GaN-based materials have emerged as promising candidates for high power and high-frequency devices. This can be attributed to their unique and attractive properties such as wide range of bandgap, high saturation velocity, spontaneous and piezoelectric polarization, and high thermal and chemical stability. The AlGaN/GaN high electron mobility transistors (HEMTs) have been extensively studied during this time. The two-dimensional electron gas (2DEG) at the AlGaN/GaN heterointerface can be achieved without doping owing to their polarization properties. Despite their promising device performances for high power and high-frequency applications, they are limited by issues such as self-heating, buffer leakage and reliability. The high current in the AlGaN/GaN HEMTs is driven through the narrow (~10 nm) 2DEG channel causing significantly high self-heating in this region, resulting in negative output conductance and decrease in carrier mobility. The increase of temperature due to self-heating deteriorates the device performance and may reach a level where it may lead to device failure. The heat-dissipation in HEMTs majorly takes place in the vertical direction. Thus, the substrate acts as the heat sink for the device, making its thermal conductivity vital. The vertical breakdown and leakage can be reduced by having better carrier confinement. The reliability issues arising from strained AlGaN barriers can be improved significantly by reducing this layer's mechanical strain. Lately, AlN(barrier)/GaN(channel)/AlN(buffer) double heterojunction (DH)-HEMTs have been explored to overcome these limitations. The AlN buffer as a back-barrier offers strong carrier confinement, reducing buffer leakage due to its large bandgap. It also improves heat dissipation due to its higher thermal conductivity. Moreover, strain-free AlN barrier is expected to improve reliability as well as vertical scaling of HEMTs. Majority of the reported AlN/GaN/AlN (AGA) DH-HEMTs exhibit sheet carrier density in the range of 2.2-3.2×1013 cm−2 with carrier mobility varying between 300-600 cm2/V.sec. The challenge is to grow a relaxed AlN back-barrier and the subsequent growth of coherently strained GaN channel and unstrained AlN barrier layers, which will be addressed in this report. In this work, simulation-based studies of DC characteristics of AlGaN/GaN HEMTs on various substrates (sapphire, Si, GaN, AlN, 4H-SiC and Diamond) were conducted to determine the most suitable substrate for the growth of AlGaN/GaN HEMTs. This was followed by the growth and characterization of AlN/GaN/AlN double heterojunction (DH) HEMT layer structures on semi-insulating 4H-SiC substrates by plasma assisted molecular beam epitaxy (PA-MBE). The higher thermal conductivities of AlN and 4H-SiC are likely to improve heat dissipation, thus providing greater thermal stability and lesser device deterioration due to self-heating. The simulations performed were based on a fabricated AlGaN/GaN HEMT on sapphire substrate. The results provided a quantitative estimation of the effect of substrate thermal properties on the DC characteristics. The lattice heat maps of HEMTs on various substrates (sapphire, Si, 4H-SiC, GaN, AlN and diamond) were analyzed for variations in channeltemperature, vertical temperature profile and the hotspot temperature. The DC characteristics of the HEMTs were enhanced as the thermal conductivity of the substrate material increased. The current degradation due to self-heating reduced remarkably from ~35% to ~18% as the substrate material was changed from sapphire to 4H-SiC. It further decreased to ~11% when diamond was used as the substrate in place of 4H-SiC. This indicated that self-heating reduced progressively as the thermal conductivity of AlGaN/GaN HEMT's substrates increased. A similar trend was observed for the rise in the hotspot temperature among the HEMTs studied. AlGaN/GaN HEMTs on diamond substrate conclusively showed the best results among the substrates studied. However, the high costs and challenges involved in the epitaxial growth of HEMTs on diamond outweigh the improvements observed when compared to 4H-SiC. Thus, 4H-SiC is the choice of substrate for the growth of AlN/GaN/AlN DH-HEMTs. The AlN/GaN/AlN DH-HEMT epilayers were optimized for the III/V ratio, growth temperature and thickness while maintaining constant N2 flow and RF power. An optimized 300 nm thick AlN buffer was grown with the initial 100 nm grown under 3D growth conditions (III/V = 0.45) followed by 200 nm growth under 2D growth conditions (III/V = 1.04) at a substrate temperature of 750 ºC. A droplet-free and crack-free surface with smooth surface morphology was achieved (RMS roughness ~0.4 nm for 5×5 μm2 AFM scan). The residual compressive stress in the AlN buffer was -1.1 GPa. The subsequent GaN channel layer was optimized to be grown at 720 ºC with minimal relaxation at nearly stoichiometric condition (III/V = 1.05).The AGA heterostructure was completed with an AlN barrier layer grown at near stoichiometric (III/V~1) growth condition and a 2 nm GaN cap layer. The AlN barrier and GaN channel combination of 3 nm and 43 nm thickness resulted in 2DEG density of 2.16×1013 cm-2 and carrier mobility of 528 cm2/V. s. Furthermore, this work reports on the carrier mobility enhancement in AlN/GaN/AlN DH-HEMTs on 4H-SiC with high sheet carrier density, by stress engineering in AlN buffer and GaN channel. A comparative study of AGA heterostructures with varying growth conditions showed that the compressive stress in the GaN channel varies non-linearly with AlN buffer stress. The 2DEG density (~ 4.1×1013 cm−2) is unaffected by the epilayers' stress variations. However, the carrier mobility increases from 183 cm2 V−1 s−1 to 613 cm2 V−1 s−1 as the GaN channel stress is increased from -3.0 GPa to -3.8 GPa, respectively. The carrier mobility enhancement in AlN/GaN/AlN heterostructure was achieved via epilayer stress engineering. The high (μ×ns) product reported in this work would lead to higher device output power density.